Micromobility: a systematic literature review on the measurement of its environmental, social, and economic impacts on urban sustainability - Dias, Gabriel José Cabral (2021)
The use of micromobility in cities has been highly associated with environmental, social, and economic benefits. These sustainability impacts can be achieved by the proper city planning before the implementation of micro vehicles, which can include pilot programs, connection to public transport to promote first-and-last mile trips, curb space management, and safety measurements. Although to better understand the real environmental, social, and economic impacts of micromobility usage in cities, some methodologies need to be used in order to measure them. Thus, this research focuses on an extensive literature review to discuss the most used methodologies to measure the sustainability impacts generated in cities by micromobility. As the results show, to measure the environmental impacts, the Life Cycle Assessment methodology can be used, followed by geospatial analysis and surveys to measure the social impacts, and conversion of health, and time-saving benefits to a monetary unit to measure the economic impacts of micro vehicles.